Democracy and Foreign Education - Spilimbergo, Antonio (IMF Working Papers; Working Paper ;, 2007)
Do foreign-educated individuals play a role in promoting democracy in their home countries? Despite the large amount of private and public resources spent on foreign education, there is no systematic evidence that foreign-educated individuals foster democracy in their home countries. Using a unique panel dataset on foreign students starting from 1950, I show that, indeed, foreign-educated individuals promote democracy in their home country, but only if the foreign education is acquired in democratic countries. The results are robust to reverse causality, country-specific omitted variables, and inclusion of a variety of control variables. The results are stronger for small countries.